Knowledge base about risk and safety of nuclear facilities to support analysts and decision-makers (Brazilian Journal of Radiation Sciences, 2021)
Epistemic uncertainty (related to lack of knowledge), often found in the documentation of nuclear facility engineering projects, can affect the decision-making process of managers and analysts on safety and risk issues. This article conceptualizes the nature of the major uncertainties involved in engineering projects and describes a knowledge base developed to gather data and information related to the project of an Open-Pool Light-water Research Reactor (OPLRR) and whose purpose is to assist professionals who work in the areas of nuclear facilities. To reduce the epistemic uncertainties that may arise in the project, the OPLRR knowledge base is designed with a set of information that allows identifying and facilitating the forwarding of solutions to address inconsistencies, and /or pending issues that may exist in the project. In this sense, the information and the documents related to the project are organized in a graphical and hierarchical architecture, allowing the knowledge base users to quickly and easily obtain information regarding the systems, processes, equipment, and components of the project. Besides that, a set of documents containing descriptions, reliability data, and some other information about the systems and components are specially created to the knowledge base and it is crucial to reduce epistemic uncertainties, once it raises the issues and the inconsistencies of the project, as well as it clarifies the interrelations between the systems, the functioning of the equipment, their failures modes and the consequences of their failures, and some other data, which are not originally contained in the documents of the project.